Sliding characteristics of bioinspired polydimethylsiloxane micropillars under bending states. (November 2022) - Liu, Shouyao; Cui, Zhibo; Su, Zhaoqian; Zhu, Bin; He, Shixue; Su, Benlong; Wu, Jian; Wang, Youshan
Abstract: Surface micropillars of soft material, inspired by biological structures, are widely designed and applicated to flexible electronics and micro/nano-robots. The surface micropillars trends to be bent during the sliding process. Herein, sliding characteristics of hexagonal polydimethylsiloxane (PDMS) micropillars under different bending states and micropillar numbers were investigated. Finite element and dynamic friction models were introduced to analyse the sliding mechanism. The friction coefficient can be adjusted by the bending states of the PDMS micropillar. The sliding characteristic is an elongating-rebounding process. The elongating process is divided into two stages (creep and peel), and the rebounding process is divided into two stages (slip and stick). The condition for mass-belt detachment is established based on the dynamic friction model. Highlights: Sliding characteristics of bioinspired polydimethylsiloxane micropillar under different bending states were investigated. Elongating-rebounding mechanism of single bending micropillar was analyzed by finite element and dynamic friction models. The friction fluctuation inhibition mechanism of bioinspired PDMS micropillar was clarified in elongating-rebounding process.